Bimbingan Perkawinan Pranikah Bagi Usia Remaja Dalam Upaya Mencegah Pernikahan Anak - Rasta Kurniawati Br Pinem; Nur Rahmah Amini; Ina Zainah Nasution (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
Marriage or marriage is a sunnatullah commanded by Allah SWT. The command to marry has a very noble purpose in accordance with Maqashid sharia, namely to maintain or maintain offspring. This goal can be achieved if the implementation is in accordance with the rules that have been set by Allah SWT as the Lord who creates and makes rules so that humans remain noble.Child marriage is a marriage that is not in accordance with the rules made by Allah SWT because to achieve the purpose of marriage, responsibility is an urgent requirement. The ability of this responsibility, of course, needs to be tested for prospective husbands and wives. Liability will be subject to legal burden, be held accountable for the trust received.Cases of child marriage are still common and even tend to increase, this happens because of the low knowledge and understanding of parents about religion, economic factors, association, culture, lack of knowledge of spro, unwanted marriage, and easy access for children to pornographic and pornographic sites.Child marriage is not justified by religion and the state. As a result of child marriage, there will be a loss of generations who will become leaders in the future. Child marriage does not bring benefits but brings harm to both the child himself and his family and country. Therefore, the State and the existing government should cooperate with religious organizations, related agencies and even the community to find solutions. All elements must work together to reduce or eradicate cases of child marriage, with the campaign being a child, don't have children.